The shape of the form and its influence on the design processes (2019)
This letter is the result of research carried out within the Program of Industrial Design at the University of Pamplona, and aims to strengthen the material culture through the study of formal configuration objects developed by small producers. This article presents in depth the main theoretical construct that supports the conceptual development not only of this project but what has become a research and under the concept of the authors can be considered an area of knowledge that influence directly own design process of design disciplines.